2010
DOI: 10.1111/j.1747-6593.2010.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Surahammar: a case study of the impacts of installing food waste disposers in 50% of households

Abstract: This paper reviews 15 years of sewage works' monitoring data to assess the effect of installing in-sink food waste disposers (FWD) and how these effects compare with the published scientific literature. For the first time, it has been possible to assess at full scale the load/cost transfer from solid-waste to wastewater management. Within a period of 10 years, 50% of households in the town of Surahammar in Sweden chose to have FWD installed as their means of managing their kitchen food waste. The drainage from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 6 publications
0
12
0
6
Order By: Relevance
“…Schemes A2 and B2 include the integration of FWDs in 50% of the households of the community. Both electricity and tap water are supplied to pump the combined stream of wastewater and DOW to the WWTP (Evans et al, 2010). Primary settling is applied after screening to separate the primary sludge from the primary effluent.…”
Section: Description Of the Treatment Schemesmentioning
confidence: 99%
“…Schemes A2 and B2 include the integration of FWDs in 50% of the households of the community. Both electricity and tap water are supplied to pump the combined stream of wastewater and DOW to the WWTP (Evans et al, 2010). Primary settling is applied after screening to separate the primary sludge from the primary effluent.…”
Section: Description Of the Treatment Schemesmentioning
confidence: 99%
“…Measurements of biological oxygen demand (BOD5) in the inlet of a wastewater treatment plant by Evans et al. () implied temporal variability in the inlet wastewater composition; however, changes in the microbial communities that are present within the supplying sewer network have seldom been investigated. The variable conditions in sewers, whether chemical or physical, can affect microbial communities in several ways.…”
Section: Introductionmentioning
confidence: 99%
“…Vollertsen et al (2005) showed large spatial variability in chemical oxygen demand (COD) fractionation of the organic matter in 109 wastewater samples collected from five different in-sewer locations in north Denmark. Measurements of biological oxygen demand (BOD5) in the inlet of a wastewater treatment plant by Evans et al (2010) implied temporal variability in the inlet wastewater composition; however, changes in the microbial communities that are present within the supplying sewer network have seldom been investigated. The variable conditions in sewers, whether chemical or physical, can affect microbial communities in several ways.…”
Section: Introductionmentioning
confidence: 99%
“…It went on to assume for the purpose of predicting impact on water resources that there would be an increase of 1 US gallon per person per day but this seems to have been arbitrary and unconnected with the actual measurements made in the field study (New York City DEP, 1999). Evans et al (2010) found the flow into a wastewater treatment works (WwTW) did not change significantly between the time when there were no FWDs and when 50% of the 3700 households used FWDs.…”
Section: Water Usementioning
confidence: 99%
“…Surahammar in Sweden provided Evans et al (2010) with an opportunity to assess the cost transfer from solid waste to wastewater, because in the space of 12 years FWD installation changed from 0% to 50% of households and throughout this period the WwTW that serves the municipality collected and analysed 4-weekly, 24-hour composite samples of the influent. The sewerage is largely separate surface and sanitary sewers with interconnection to relieve excess flow.…”
Section: Cost Transfer To Wastewater Treatmentmentioning
confidence: 99%